School grade and sex differences in domain-specific sedentary behaviors among Japanese elementary school children: a cross-sectional study - Kaori Ishii; Ai Shibata; Minoru Adachi; Yoshiyuki Mano; Koichiro Oka (BMC, 2017)
Abstract Background It is vital to reduce the proportion of sedentary behavior in children. Understanding the duration and behavioral context is needed. The present study examined school-grade and sex differences in domain-specific sedentary times and concurrence with screen-time guidelines among Japanese elementary school children. Methods A total of 625 children (330 boys) were surveyed in 2010 and 2014. Using a questionnaire, data regarding participants' grade (first through third grades: lower grades; fourth through six grades: higher grades), sex, weight, and height were collected in addition to the time spent per day engaging in each specific sedentary behavior separately: (1) reading or listening to music, (2) TV or video viewing, (3) TV game use, (4) internet use excluding class, (5) homework, and (6) car travel. Two-way analysis of covariance and logistic regression analyses, adjusted for BMI and moderate to vigorous physical activity, were used to examine school-grade and sex differences in sedentary behaviors and the independent risk of exceeding recommended total daily screen time (< 2 h). Results On 625 children, mean minutes (SD) of sedentary behavior per week in (1) - (6) were 90.3 (123.4), 535.0 (356.6), 167.3 (222.1), 23.9 (70.9), 264.9 (185.3), and 33.4 (61.2) in weekdays and 42.1 (70.0), 323.9 (232.0), 123.0 (96.4), 15.8 (49.9), 74.4 (96.4), and 71.3 (84.9) in weekends, respectively. There were differences in the minutes of sedentary behavior between participants of 2010 and 2014; e.g., TV game use and homework in weekdays and weekdays and car travel in weekends. Boys spent more time in TV game use, and girls spent more time reading, listening to music, doing homework, and car travel. Higher-grade students spent more time reading or listening to music, using a computer, and doing homework. Higher-grade students were 2.09 times (95% CI: 1.32 − 3.30) in whole week, 2.08 times (95% CI: 1.45 − 3.00) in weekday, and 1.88 times (95% CI: 1.29 − 2.74) in weekend more likely to spend ≥2 h per day in domains (2) − (4) (screen-time) than lower-grade students. Conclusions Time spent engaging in each domain-specific sedentary behavior differed according to sex and school grade. Higher-grade students were less likely to meet screen-time guidelines. These findings highlight the need for domain-focused strategies to decrease sedentary behavior in Japanese school-age children.